Advances in modelling gold nanoparticle radiosensitization using new Geant4-DNA physics models. (13th November 2020) - Engels, Elette; Bakr, Samer; Bolst, David; Sakata, Dousatsu; Li, Nan; Lazarakis, Peter; McMahon, Stephen J; Ivanchenko, Vladimir; Rosenfeld, Anatoly B; Incerti, Sébastien; Kyriakou, Ioanna; Emfietzoglou, Dimitris; et al.
Abstract: Gold nanoparticles have demonstrated significant radiosensitization of cancer treatment with x-ray radiotherapy. To understand the mechanisms at the basis of nanoparticle radiosensitization, Monte Carlo simulations are used to investigate the dose enhancement, given a certain nanoparticle concentration and distribution in the biological medium. Earlier studies have ordinarily used condensed history physics models to predict nanoscale dose enhancement with nanoparticles. This study uses Geant4-DNA complemented with novel track structure physics models to accurately describe electron interactions in gold and to calculate the dose surrounding gold nanoparticle structures at nanoscale level. The computed dose in silico due to a clinical kilovoltage beam and the presence of gold nanoparticles was related to in vitro brain cancer cell survival using the local effect model. The comparison of the simulation results with radiobiological experimental measurements shows that Geant4-DNA and local effect model can be used to predict cell survival in silico in the case of x-ray kilovoltage beams.